FAKTOR FAKTOR YANG MEMPENGARUHI KETERLAMBATAN PENETAPAN ANGGARAN PENDAPATAN DAN BELANJA DESA - Udiono, Bambang (Master of Public Administration, Universitas Slamet Riyadi, 2021)
This study aims to describe and analyze the factors that influence the delay in determining the Village Revenue and Expenditure Budget. The type of research used is qualitative research with the opinion theory of Subechan et al (2014) and Natalia Gradiana Aunsuni (2019). Indicators of factors that influence the delay in determining the Village Revenue and Expenditure Budget are commitment factors, coordination factors, competency factors and infrastructure. Methods of data collection are carried out through interviews, observation and documentation. The results showed that the delay in determining the Village Revenue and Expenditure Budget that occurred in Wagir Lor Village, Ngebel District, Ponorogo Regency was influenced by the Commitment of the Village Head and Village Consultative Body which was still not optimal, the coordination of the Village Head with the Devices was not fully running well, the Competence of Village Officials showed some still do not understand their main duties and functions, the existence of Village Office Facilities and Infrastructure is an important factor in the activities of implementing Village Government.